PENETAPAN ASAL USUL ANAK TANPA MELALUI TES DNA BESERTA AKIBAT HUKUMNYA (IAIN Tulungagung, 2022)
Marriage is seen as a sacred event and a significantmilestone in human life, and religious components arecrucial to its continuation. Marriage Law Number 1 of1974 takes into account interfaith unions. But becausetheir original dads frequently do not accept them,illegitimate children can cause issues in society withrelation to accountability, such as who is responsiblefor providing for the children's financial support, care,and education. In this research of legal ramificationsand determining a child's origin without using a DNAtest are examined. The study adopts a normative legalapproach. The study's findings indicate that Article 43Paragraph 1 of the Constitution regulates therequirements of life and defines what is meant by achild born outside of wedlock as having a legal statusthat is limited to a civil relationship with the motherand her family. Legally speaking, children's financialand material well-being is the responsibility of theirmother and her family. However, as noted in theConstitutional Court Decision No. 40/PPU-VIII/2010,biological fathers are also legally required to takecare of, raise, and care for children born outside ofmarriage if they do not accept the child's status